Comprehensive typhoon hazard zoning in China based on historical records - Zhao Liu; Liyan Xu; Qing Lu (Geomatics, Natural Hazards & Risk)
The formulation of nationwide goals, strategic plans, and specifically zoned areas for typhoon hazard mitigation and prevention is paramount for addressing the threat in a spatially explicit manner. Utilizing historical rainfall and wind speed data associated with typhoon disasters in the Northwest Pacific and South China Sea from 1949 to 2017, we proposed a comprehensive typhoon hazard zoning delineated based on the assessment of typhoon disaster risks, considering hazard-causing factors, hazard-formative environments, and hazard-bearing bodies through an Analytic Hierarchy Process. High-risk areas were primarily located in the coastal regions of South and Southeast China. Medium-risk areas were situated in the Yangtze River Delta and towns adjacent to Bohai Bay. Low-risk areas were primarily located in the central region of Guangxi, the Guangdong-Hong Kong-Macao Greater Bay Area, the vicinity of Fuzhou, the majority of southern Jiangsu and northern Zhejiang, all of Shanghai, the northern and southern parts of the Shandong Peninsula, the area around Bohai Bay in Tianjin, a minor portion of Hebei, and the three northeastern provinces. Appropriate mitigation measures were proposed to address the threats posed by typhoons in these regions. This information is instrumental in providing reliable support for China in addressing the challenges posed by typhoons.